The Influence of Ethnocentrism on EFL Students’ Cultural Behavior The case of Master One Students of English at Amar Thelidji university in Laghouat - Koubci ,NABIL; Mecheri ,SAMIA; Cherfaoui ,SAMIA (Faculty of Letters and Foreign Languages Department of English, 2019)
This research discusses ethnocentrism and cultural relativism which are defined as a sociocultural phenomenon, the beliefs, attitudes and practices learnt through membership of a cultural group, which constrains how its members view non-members or outsiders. So it is important to facilitate the student's understanding of civilization and to determine whether or not the student is aware that the world has become almost unipolar, and the language he is studying become a vehicle of the Western civilization .So, we shed the light on this phenomenon by highlighting the concepts , mainly ethnocentrism and cultural relativism, and to investigate if the students are ethnocentric, hooked to their culture and against Western behavior, or they have a culture of proportion so that they have the ability to integrate, adopt and why not imitate certain customs and traditions. A descriptive and analytical study is chosen to prove or disprove this hypotheses, the data is collected from master 1 LMD students at English department of Amar Thelidji Laghouat University. To determine their awareness about the impact of English in their life. The results were positive and confirmed the validity that students are aware of all awareness through their cultural and religious backgrounds, they like English language and study it through history and culture, but they have no objection to applying certain positive acceptance behaviors to each other, but they do not forget their origins